BURDEN OF DISEASE OF HYPERTENSION IN THE PHILIPPINES PROJECTED IN 2050. (June 2022) - Mercado-Asis, Leilani; Ona, Deborah Ignacia; Bonzon, Dolores; Vilela, Gilbert; Diaz, Alejandro; Balmores, Benjamin; Co, Marlon; Mina, Arnold Benjamin; Cabral, Esperanza; Aquino, Abdias; Abelardo, Nelson; Gomez, Lynn; et al.
Abstract : Objective: The burden of disease attributable to hypertension in the Philippines has continuously increased over the last three (3) decades. In spite of this, the burden accounted for by hypertension is investigated to a lesser extent in the Philippine context. This study was carried out to ascertain the economic impact of hypertension if people within the productive years are affected and the results projected in the next 30 years. Design and method: Accordingly, data triangulation using interviews from 806 patients, vis-à-vis sources such as Philippine Statistics Authority (PSA), Family Income and Expenditure Survey (FIES), National Demographic and Health Survey (NDHS), National Nutrition Survey, Institute for Health Metrics and Evaluation (IHME), United Nations World Population Prospects, World Health Organization (WHO) and Labor Force Survey were employed. Consequently, cost of illness (COI) was calculated using the direct costs, morbidity costs, and mortality costs. Results: In 2020, about 70% of total economic burden are accounted for direct & indirect care. In the next 30 years (2020 - 2050), the economic cost of hypertension in present value is expected to increase from Php52.6. billion in 2020 to Php97.3 billion by 2050. The productivity of majority of the patients (60 - 78%) was affected most especially in household and missing work. The productivity loss due to premature mortality accounts for about 17% of total economic burden in 2020 and this is expected to increase to 20% by 2050. Conclusions: The economic cost of hypertension will almost double in the next 30 years. Both productivity loss and premature mortality will have a significant impact on the Philippine economy by 2050. This calls for a robust collaborative and cooperative participation of both governmental and nongovernmental agencies to thwart the looming effect of a controllable disease like hypertension on the ocio-economic status of the country and on public health in general.